2014
DOI: 10.2500/ar.2014.5.0100
|View full text |Cite
|
Sign up to set email alerts
|

Sinonasal Phosphaturic Mesenchymal Tumor: Case Report and Systematic Review

Abstract: We report a case of sinonasal phosphaturic mesenchymal tumor (PMT) and conduct a systematic review of the literature to highlight a unique paraneoplastic syndrome associated with PMT. We used English language publications from Medline and Cochrane databases (1970–2013) as data sources. A systematic review of the literature was conducted. All reported cases of head and neck PMTs were included. The presence or absence of the associated paraneoplastic syndrome was noted. We found 33 cases of PMT in the head and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 44 publications
3
39
0
1
Order By: Relevance
“…Only one of the tumors in our series was originally diagnosed as PMT, a pattern consistent with previously published studies [1,5,10]. Tumors arising in the head and neck may be more prone to misdiagnosis as these sites are often biopsied and the small amount of material provided may not demonstrate features that distinguish PMT from similar tumors.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Only one of the tumors in our series was originally diagnosed as PMT, a pattern consistent with previously published studies [1,5,10]. Tumors arising in the head and neck may be more prone to misdiagnosis as these sites are often biopsied and the small amount of material provided may not demonstrate features that distinguish PMT from similar tumors.…”
Section: Discussionsupporting
confidence: 74%
“…Tumors involving the head and neck are extremely rare [3,[5][6][7][8][9]. Half of all PMTs reported in the head and neck have involved the sinonasal tract; other sites include the pharynx, maxilla, mandible, tongue, floor of mouth, and posterior neck.…”
Section: Introductionmentioning
confidence: 99%
“…The most common location for PMT involves the extremities (95 %) followed by head and neck (H&N) sites (5 %) with the sinonasal cavity representing more than half of the cases [9,10]. There is a roughly equal distribution between hard and soft tissue with perhaps a slight predilection in bone (53 %) [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…A total of 4 cases (57.14%) had recurrence during the follow-up. [6,9,10] In our study, the biochemical indicators of case 1 showed no abnormities which made diagnosis di cult.…”
Section: Discussionmentioning
confidence: 53%